DAYA TARIK ENDORSERNOAH TERHADAP BRAND IMAGEIKLAN KARTU XL - Retnaningtyas, Ester; Hastasari, Chatia; Pratiwi, Dyah Retno (KOMUNITAS, 2014)
Nowadays,Â  almostÂ  allÂ  ofÂ  televisionÂ  commercialsuseartistsasendorser.Â  TheÂ  endorserÂ  isÂ  selected basedÂ  onÂ  its attraction.Â  TheyÂ  has a duty inintroducing theÂ  brandÂ  ofÂ  a product. XL is one of the advertisement which use artist as an endorser. XL uses NOAH as an endorser because NOAH is considered having capability in creating brand image XL. The success in building the brand image is also determined by consumer perceptions of endorser who became icon is in the advertisement. Therefore, this research focus on analysis of is there any influence of NOAH attraction to brand imageÂ  ofÂ  XLÂ  advertisementÂ  amongÂ  SahidÂ  SurakartaÂ  UniversityÂ  studentÂ  classÂ  2011. The populationsÂ  of thisÂ  study is allof students inclass 2011Â  atÂ  SahidÂ  SurakartaÂ  University.Â  TheÂ  total number of student is 295. Where as, the sampling techniques was used a simple random sampling (the taking of sample from population was randomlyÂ  without regard to the existing strata in the population). This research used respondenceâs questionnaire as the primary data. Meanwhile, in analizingÂ  influenceÂ  ofÂ  NOAHÂ  attractionÂ  toÂ  brandÂ  imageÂ  ofÂ  XLÂ  advertisementÂ  amongÂ  Sahid SurakartaÂ  UniversityÂ  studentÂ  classÂ  2011Â  wasÂ  useÂ  Rank-OrderÂ  Correlation.Â  TheÂ  ResultsÂ  ofÂ  this studyshows that results Spearmens coefficient Rho=0.426 and p-value of 0.000. Thus,p-value less thanÂ  0.05Â  itÂ  means thatÂ  there is significant influence of NOAHÂ  attraction toÂ  brand imageÂ  of XL advertisement among Sahid Surakarta University student class 2011.